2015
DOI: 10.1007/s00246-015-1214-5
|View full text |Cite
|
Sign up to set email alerts
|

Regional Stress-Induced Ischemia in Non-fibrotic Hypertrophied Myocardium in Young HCM Patients

Abstract: The relationship between hypertrophy, perfusion abnormalities and fibrosis is unknown in young patients with hypertrophic cardiomyopathy (HCM). Since mounting evidence suggests causal relationship between myocardial ischemia and major adverse cardiac events, we sought to investigate whether (1) regional myocardial perfusion is decreased in young HCM patients and in individuals at risk of HCM, and (2) hypoperfused areas are larger than areas with fibrosis. HCM patients (n = 12), HCM-risk subjects (n = 15) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…The results of our study indicate that the myocardial perfusion of patients with HCM, diabetes, or hypertension is abnormally lower than that of healthy individuals. This is in accord with other recent values reported in the literature …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results of our study indicate that the myocardial perfusion of patients with HCM, diabetes, or hypertension is abnormally lower than that of healthy individuals. This is in accord with other recent values reported in the literature …”
Section: Discussionsupporting
confidence: 94%
“…Earlier studies using PET/SPECT, first‐pass MR, or late gadolinium enhancement showed abnormal myocardial microcirculation, myocardial replacement fibrosis in HCM, diabetes, and hypertension, even if without obstruction of epicardial coronary arteries . It is very important to evaluate myocardial microcirculation for these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, when using mitral E/e´ > 8 as a cut-off for LV diastolic dysfunction, we found higher levels of ICTP ( p = 0.02) in the HCM group, a finding that could suggest alterations in ECM prior to development of fibrosis. As recently reported [ 31 ], the degree of myocardial fibrosis was assessed using CMR -LGE, and the association between regional hypoperfusion and fibrosis [ 39 ] in young patients with HCM. In line with previous studies showing a certain correlation between the magnitude of fibrosis and the degree of hypertrophy [ 2 , 7 9 ], fibrosis was predominantly found in myocardial segments with advanced hypertrophy [ 39 ] and also indicating a pathology beyond LVH and LGE by showing greater extent of areas with impaired myocardial perfusion even in non-fibrotic myocardium during adenosine hyperemia indicating regional hypoxemia, suggesting an important relationship of myocardial hypoperfusion with fibrosis occurrence in HCM [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether these markers are evidence for early fibrosis, early endothelial dysfunction, or myocyte remodeling process, is still questionable and should be more extensively investigated. Although energy impairment may be the initial catalyst, the degree of hypertrophy correlates directly with stress-induced or vasodilator-induced ischemia, whereas energy impairment does not [29, 49, 61]. Ischemia can also be seen in regions of non-hypertrophied myocardium, potentially heralding extension of remodeling in those regions as well [26, 109].…”
Section: Microcirculatory Alterations and Prehypertrophymentioning
confidence: 99%